12.2 ABNORMAL SENSITIVITY TO TIME ASYNCHRONIES LEADING TO BODILY SELF DISORDERS?. (9th April 2019) - Giersch, Anne; Duval, Celine; Krieg, Julien; Schwitzer, Thomas; Marques-Carneiro, Eduardo
Abstract: Background: The sense of time continuity is a given, and we usually do not think about it. Yet, the patients' self-reports and the phenomenological analysis of their verbal descriptions suggest that patients with schizophrenia experience a breakdown of the experience of time continuity. Such a breakdown may originate a disorder of the 'bodily' self, inasmuch the ability to feel oneself as one unique being requires this feeling to be extended over time and continuous. We will argue that this involves prediction mechanisms, to transform a series of discontinuous events into a fluent sequence, and we will summarize previous studies suggesting that these mechanisms are impaired in patients with schizophrenia. We checked the hypothesis that time prediction difficulties make patients abnormally sensitive to short asynchronies that they cannot integrate into a fluent sequence of events. Methods: We used a typical task consisting in showing two squares on a computer screen, simultaneously or with an asynchrony between 24 to 96 ms (steps of 24 ms). Subjects (32 stabilized patients with schizophrenia and 29 controls) were required to decide whether the squares were simultaneous or asynchronous and to press on a right or left square accordingly. We used 108 trials per condition to allow for EEG recording, learning effects, and to compute trial-to-trial effects. Trial-to trial effects were aimed at exploring prediction mechanisms directly, by checking how subjects adapt to a given asynchrony in order to adjust their processing of the subsequent squares' sequences. Results: Behavioral results showed that the performance of patients was impaired when the task required the detection of asynchronies, rather than simultaneity. Performance degraded over time and patients had difficulties to detect large asynchronies at the end of the test. They were slowed down relative to controls in case of asynchronies, but not in case of simultaneous squares. Trial-to-trial effects showed that controls' performance was modulated more than patients' after having detected an asynchrony. The detection of an asynchrony facilitated the detection of large asynchronies in controls (but not in patients) and slowed down the detection of simultaneity. In EEG, the P300-like component (230-320ms) at right central and centro-parietal sites increased in amplitude with asynchronies in controls but not in patients, which could be related to the performance deterioration at large asynchronies in patients. At short asynchronies (24 ms), a large N2-like component (160–200 ms) was selectively observed in patients at left frontal electrodes. Conclusions: The results are consistent with the hypothesis that controls learn to use asynchronies to predict and improve the processing of subsequent asynchronies. In contrast, patients do not appear to benefit from these prediction abilities. It is as if patients prepare for simultaneities instead of asynchronies. Moreover, patients show ample reactions to 24 ms asynchronies, as if abnormally sensitive to short asynchronies that are subthreshold. Such sensitivity might be invalidating, inasmuch information must be integrated and synchronized in order to enable interactions with the outer world, i.e. immersion in the world. Abnormal sensitivity to short asynchronies may be related to a difficulty to produce coherent sequences of information. As a whole these difficulties may alter the patients' immersion in the world, and thus contribute to bodily self-disorders.